The Effect of Pricing Policy and Service Quality on Customer Satisfaction at Bunga Laundry in Surabaya Village, Bengkulu City (Case Study on Customers of Bunga Laundry in Surabaya Village, Bengkulu City) - Merta Kusuma; Afriana Ananda Putri (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
This study aims to determine the effect of pricing policies and service quality on customer satisfaction in laundry flowers in the Surabaya urban village, Bengkulu city (a case study in laundry interest customers in the Surabaya urban village, Bengkulu city), either partially or simultaneously. There are several factors that will be discussed in this study, including pricing policies and service quality. The objects in this study were customers at Laundry Flowers in the Surabaya Village, Bengkulu City, totaling 140 people. In this research the writer uses data collection methods by means of observation, interviews and questionnaires. There are several data analysis techniques used in this study, namely instrument testing namely validity test, reliability test, classical assumption test, coefficient of determination, and also hypothesis testing. From the results of the multiple linear regression test, the regression equation is as follows: Y = 2.242 + 0.567 (X1) + 0.416 (X2). From the hypothesis test, namely the T test that has been carried out, it can be seen that the variable Pricing Policy (X1) obtained a tcount of 7.180 (higher than the value of ttable, or ttable > 1.97743 (see distribution in table t), and a significance level of 0.000 (significant <0.05) and the variable Quality of Service (X2) obtained a tcount of 7.350 (lower than the value of ttable, or ttable <1.97743 (see distribution in table t), and a significance level of 0.000 (significant > 0.05). So it can be concluded that the hypothesis is accepted, meaning that there is a partial influence between the Pricing Policy (X1) and Service Quality (X2) on the Customer Satisfaction variable (Y).From the F test it is known that the Pricing Policy variables (X1) and Service Quality (X2) are obtained fcount of 114.545 (higher than the ftable value, or ftable > 2.67 (see distribution in table f), and a significance level of 0.000 (significant <0.05). This means that together the variables l Pricing Policy (X1) and Service Quality (X2) have an effect on Customer Satisfaction (Y) on Laundry Flowers in the Surabaya Village, Bengkulu City.